In brevi quasi tabella immagini e strategie retoriche nella storiografia di Floro - Chiara Renda (Testi: Antichità, Medioevo e Umanesimo, 2020)
Florus' work has always been regarded as a summary of Livy's broader narrative, reorganized around a "biological" conception of history to become more effective. The design of his historical account, however, is the result of a series of strategies outlined by the author himself in his praefatio. There Florus reveals his methodology to the reader by declaring that he intends to operate like "those who paint the regions of the earth." My analysis of this work shows that Florus sacrifices the accuracy of historical information in order to present the Roman history from the origins to the Augustan age as a coherent trajectory that justifies the Empire. On the one hand, this path is made "visible" through the use of an "evolutionary" narrative pattern, characterized by the transition between different aetates; on the other hand, it can be defined as "geographical," for it mirrors the Roman imperialistic expansion. The only break in this linear narrative is the account of the civil wars from the age of the Gracchi onward, recounted all together in Book 2 for the sake of clarity. In this case Florus employs a new strategy, that shatters the chronological arrangement of the material to privilege the discussion of agonizing ethical considerations. This monograph also examines the stylistic choices adopted by Florus throughout his narrative. The use of the metaphor and the direct intervention of the author, who comments on particular events or characters, inserting questions and interjections, create an original synthesis of history and rhetoric that aims at gaining the reader's approval. Florus' resorting to techniques commonly employed in declamations speaks to the artistic value of his work